Handbook of EMDR and family therapy processes - Kaslow, Florence Whiteman; Maxfield, Louise; Shapiro, Francine (Wiley Online Library., 2007)
Starting with the Foreword by Daniel Siegel, MD, the Handbook demonstrates in superb detail how you can combine EMDR's information processing approach with family systems perspectives and therapy techniques. An impressive and needed piece of work, Handbook of EMDR and Family Therapy Processes provides a clear and comprehensive bridge between individual and family therapies.